2012
DOI: 10.1002/jpln.201100076
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of a Luvisol for different long‐term fertilization treatments: II. Microscale behavior and its relation to the mesoscale

Abstract: We determined the impact of different fertilization, namely organic vs. mineral fertilization, on the mesoscale parameter cyclic compressibility as well as on rheology of soil samples as a microscale parameter and how these parameters are related. Therefore, undisturbed samples were taken from a long-term fertilization trial at the Dikop farm near Bonn (Germany) and tested for their mechanical and hydraulic properties. This paper examines the sensitivity of the soil towards cyclic loading (mesoscale) and oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The effect of these factors on soil mechanical resistance can be evaluated by rheological parameters obtained in amplitude sweep tests under conditions of oscillatory shear as the deformation limit (γ L ), which represents elasticity (recoverable strain) (Mezger, 2014); the maximum shear stress (τ max ), which characterizes the maximum resistance (Holthusen et al, 2012a); and the integral z, which represents structural stiffness (Markgraf et al, 2012). Several recent studies have shown that increasing water tension increases the structural strength of soils with different textures and mineralogy, observed by the increase in these parameters Horn, 2006, 2007;Holthusen et al, 2010Holthusen et al, , 2012c Rev Bras Cienc Solo 2016;40:e0150286 2012; Baumgarten et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of these factors on soil mechanical resistance can be evaluated by rheological parameters obtained in amplitude sweep tests under conditions of oscillatory shear as the deformation limit (γ L ), which represents elasticity (recoverable strain) (Mezger, 2014); the maximum shear stress (τ max ), which characterizes the maximum resistance (Holthusen et al, 2012a); and the integral z, which represents structural stiffness (Markgraf et al, 2012). Several recent studies have shown that increasing water tension increases the structural strength of soils with different textures and mineralogy, observed by the increase in these parameters Horn, 2006, 2007;Holthusen et al, 2010Holthusen et al, , 2012c Rev Bras Cienc Solo 2016;40:e0150286 2012; Baumgarten et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The τ max indicates the maximum soil shear strength (Holthusen et al, 2012b), which was greater for the clayey soils in this study. Soil shear strength may also increase with increasing ρ B (Holthusen et al, 2012a), but for our soils, τ max and τ LVE increased with clay content even with very low ρ B values (especially, Oxisol 1 and Vertisol) (Table 1). Thus, the Oxisol 2, clayey and with comparatively highest bulk density (1.10 kg m −3 , Table 1) had the highest τ LVE and τ max .…”
Section: Rheological Propertiesmentioning
confidence: 70%
“…The higher values of γ LVE in the Vertisol probably derive from higher total carbon content (TC) as well as from high clay content and the presence of smectite. Carbon acts as a strong binding agent increasing soil stability (Six et al, 2004;Bronick and Lal, 2005;Kögel-Knabner et al, 2008;Holthusen et al, 2012a). This effect was confirmed by a decrease in γ LVE in soils subjected to oxidation of SOM to determine the stabilizing effect of SOM (Markgraf and Horn, 2007).…”
Section: Rheological Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…Chenu et al, 2000;De Gryze et al, 2005;Denef et al, 2002;Six et al, 2002), but also on the particleparticle-scale. Holthusen et al (2012a) examined the impact of organic and mineral fertilization on the rheological behavior of soils from a long-term fertilization trial (Bonn, Germany) and corroborated a decreased sensitivity towards oscillatory shearing with increasing organic matter content. The rheological response of natural slurries was investigated based on rotational experiments by Carotenuto et al (2015), who reported a decrease in viscosity and yield stress upon the selective removal of soil organic carbon.…”
Section: Physicochemical Parametersmentioning
confidence: 86%